Relationships between lifestyle and dental health behaviors in a rural population in Japan - Harada S, Akhter R, Kurita K, Mori M, Hoshikoshi M, Tamashiro H, Morita M. (Blackwell Synergy, 2005)
The aim of this study was to determine associations of lifestyle with dental health behaviors such as tooth brushing frequency, use of extra cleaning devices, and regular dental visits to a dentist.